i) Given
"\\ \\ \\ z=\\sqrt{2x+a}+\\sqrt{2y+b} \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ (1)"Differentiate (1) partially with respect to "x"
Differentiate (1) partially with respect to "y"
From (2) and (3)
Substitutiing in (1) we get
ii) Given
Differentiate (4) partially with respect to "x"
Differentiate (4) partially with respect to "y"
"\\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ z{\\partial z \\over \\partial y}=\\lambda(1+\\lambda^{-1}) \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ (6)"
From (5) and (6)
Then
"{1 \\over p}+{1 \\over q}={z \\over 1+\\lambda^{-1}}+{z \\over \\lambda(1+\\lambda^{-1})}"
"{1 \\over p}+{1 \\over q}=z{\\lambda+1 \\over \\lambda(1+\\lambda^{-1})}"
"{1 \\over p}+{1 \\over q}=z{\\lambda+1 \\over \\lambda+1}"
Hence
Show that the complete integral (ii) is the envelope of one parameter sub-system obtained by taking
Given
Then
"{\\partial f \\over \\partial a}={1 \\over 2\\sqrt{2x+a}}+{1 \\over 2\\sqrt{2y+b}}\\cdot{db \\over da}=0"
"\\sqrt{2y+b}=-{db \\over da}\\sqrt{2x+a}"
Let
"b=-{a \\over \\lambda}+c"Then
"2y+b={2 \\over \\lambda^2}x+{1 \\over \\lambda^2}a"
"z=(1+{1 \\over \\lambda})\\sqrt{2x+a}"
"z^2={(1+\\lambda)^2 \\over \\lambda^2}(2x+a)"
If
Then
"{1+\\lambda \\over \\lambda}(2x+a)=2x+\\lambda(2y)-{\\lambda \\over 1+\\lambda}\\mu"
"2(1+\\lambda)x+(1+\\lambda)a=2\\lambda x+\\lambda^2({2 \\over \\lambda^2}x+{1 \\over \\lambda^2}a-b)-{\\lambda^2 \\over 1+\\lambda}\\mu"
"(1+\\lambda)a=a-\\lambda^2b-{\\lambda^2 \\over 1+\\lambda}\\mu"
"b=-{a \\over \\lambda}-{\\mu \\over1+\\lambda}"
The complete integral (ii) is the envelope of one parameter sub-system obtained by taking
Comments
Leave a comment